2013
DOI: 10.1073/pnas.1313965110
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum phosphoethanolamine methyltransferase is essential for malaria transmission

Abstract: Efficient transmission of Plasmodium species between humans and Anopheles mosquitoes is a major contributor to the global burden of malaria. Gametocytogenesis, the process by which parasites switch from asexual replication within human erythrocytes to produce male and female gametocytes, is a critical step in malaria transmission and Plasmodium genetic diversity. Nothing is known about the pathways that regulate gametocytogenesis and only few of the current drugs that inhibit asexual replication are also capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 23 publications
2
72
0
Order By: Relevance
“…LysoPC uptake is drastically reduced in gametocytes 16 , suggesting that PMT activation is both a general response to nutrient depletion and preparation for increased requirement of this alternative substrate arm during gametocyte development. Indeed, previous work has demonstrated that PMT is essential for gametocyte maturation and mosquito infection 30, 31 .…”
Section: Discussionmentioning
confidence: 99%
“…LysoPC uptake is drastically reduced in gametocytes 16 , suggesting that PMT activation is both a general response to nutrient depletion and preparation for increased requirement of this alternative substrate arm during gametocyte development. Indeed, previous work has demonstrated that PMT is essential for gametocyte maturation and mosquito infection 30, 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme Assays and Isothermal Titration Calorimetry-Standard assay conditions for PMT activity were 0.1 M Hepes-KOH (pH 8), 2 mM Na 2 EDTA, 10% glycerol, 2.5 mM AdoMet (100 nCi of [methyl- 14 C]AdoMet), and 5 mM phosphobase substrate (either pEA or pDME) in 100 l. Protein (10 g) was incubated for 10 min at room temperature with reactions terminated and product quantified as described previously (8,9). Steady-state kinetic analysis of wild-type and mutant PfPMT was performed as described previously (8,9,18).…”
Section: Methodsmentioning
confidence: 99%
“…PfPMT plays an important role in the metabolism of the malaria parasite by supporting the synthesis of phospholipids during reproduction and growth. Disruption of the PfPMT gene leads to a reduced phosphatidylcholine synthesis from serine, growth and survival defects, and the loss of parasite transmission to mosquitoes (12)(13)(14). Because of its critical role in Plasmodium and the lack of PMT homologs in mammals, PfPMT, along with other enzymes in phospholipid metabolism, is a target for antiparasitic drug development (5,6,(15)(16)(17).…”
mentioning
confidence: 99%
“…More proteins associated lipid metabolism is in agreement with a significant increase and compositional change of lipids in gametocytes (43,44). Of them, three signal lipidassociated proteins (phosphoethanolamine methyltransferase, cytidine diphosphate-diacylglycerol synthase and calponin homology domain-containing protein) have been studied, showing that the disruption of these genes resulted in the arrest of gametocyte development (37,80). The mechanisms underlining these biological disparities between these Plasmodium species remain to be further elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…Another member of AP2 family, AP2-G2, may regulate gametocyte development by repression of specific transcripts for asexual and stages beyond gametocyte development (26). In order to prepare for rapid changes and subsequent development in free-living environment in mosquito, gametocytes adopt several strategies including storage of "maternal" mRNAs by the DOZI and possibly Puf protein complexes that can be mobilized rapidly upon stage transition (27)(28)(29)(30)(31), increased expression of protein kinases and phosphatases responsible for signal transduction (32)(33)(34)(35)(36)(37)(38), and activation of tricarboxylic acid cycle and lipid metabolism for energy and lipid requirements (39 -44).…”
mentioning
confidence: 99%